Exit strategy after percutaneous nephrolithotomy: impact of tube size with early removal compared to tubeless percutaneous nephrolithotomy — the debate continues - Ihab S. Khewkah; Raed H. Afiet; Haidar H. Al Jabban (Počki)
Background. Many studies have demonstrated the efficacy and safety of tubeless and totally tubeless percutaneous nephrolithotomy (PCNL), trying to avoid putting a nephrostomy tube (NT) to decrease patient discomfort and shorten hospital stay. However, given that nephrostomy tube serves a safety backup plan for adverse events like residual stone and intraoperative bleeding, it is worth investigating different tube size if we want to bridge the night (early tube removal) and compare it to tubeless PCNL. The purpose was to evaluate the effect of tube size (with early removal) on postoperative course compared to NT free. Materials and methods. During the period from December 2020 to June 2022, 177 patients with renal stones were selected to undergo PCNL and were prospectively followed up. At the end of procedure, the patients were randomly distributed into 3 groups. Group A, those with placement of an 18Fr NT, group B, those with placement of an 8Fr tube and group C, nephrostomy-free. For group A and B, the nephrostomy was left in place for 1 day. For group C, manual compression was applied to the flank for few minutes and the skin puncture was closed with one stitch. The groups were compared for post-operative hematocrit drop, urine leakage, need for additional analgesia and any other postoperative events. Results. The mean age for group A was 34.110 ± 6.919 years, group B was 38.670 ± 9.935 years and group C was 37.270 ± 10.657 years (F = 3.567, p = 0.03). The post hoc Tukey analysis showed a significant difference between groups A and B (p = 0.036), however, no differences were recorded between groups A and C (p = 0.203) or B to C (p = 0.714). The present study showed that the mean stone burden was 34.03 ± 5.40 mm for group A, 33.43 ± 5.60 mm for group B and 33.43 ± 4.90 mm for group C, with no significant differences (p = 0.773). The post hoc Tukey analysis showed no significant difference between groups A and B (p = 0.818), A and C (p = 0.815), B and C (p = 0.857). The male percentage was 52.3, 58.7 and 55.1 % for group A, B and C, respectively. In this study, the duration of hematuria was 6.28 ± 2.94 hours for group A, 8.80 ± 3.45 hours for group B and 13.67 ± 2.40 hours for group C, these results were statistically significant (p < 0.0001). The post hoc Tukey analysis showed a significant difference between groups A and B (p = 0.0002), A and C (p = 0.0000), groups B and C (p = 0.0000). In the current study, the mean postoperative hematocrit drop for group A was 0.60 ± 0.14 mg/dl, 0.82 ± 0.20 mg/dl for group B and 1.33 ± 0.25 mg/dl for group C. These results were statistically significant (p < 0.0001). The post hoc Tukey analysis showed a significant difference between groups A and B (p = 0.0002), A and C (p = 0.0000), groups B and C (p = 0.0000). Conclusions. Large bore NT (18Fr) for short duration (one day) provide superior bleeding control and comparable postoperative analgesic requirement and urine leak when compared to small bore NT (8Fr) and NT free. It also keeps the chance for second look nephroscopy if needed.